Multilingual Singing in Nigeria: Examining Roles, Meaning, and Function in Wazobia Gospel Music - Adekunle Oyeniyi (Religions, 2024)
This article presents an introductory historical, sociolinguistic, and ethnographic study of “Wazobia gospel music”, a twenty-first-century Nigerian congregational musical genre. The term ‘Wazobia’ signifies a fusion of the three regionally recognized local languages in Nigeria: Wa (Yorùbá), Zo (Hausa), and Bia (Igbo)—words that mean ‘come’ in the respective languages. In the Nigerian context, the Wazobia concept could also symbolize the inclusion of more than one ethnicity or language. By dissecting three multilingual Nigerian congregational songs, I unveil the diverse perceptions of Wazobia gospel music and the associations of the musical genre in line with the influencing agencies, text, and performance practices. Furthermore, I provide a detailed description and analysis of the textual and sonic contents of Wazobia gospel music, emphasizing its roles, meanings, and functions in the Lagos congregations context. I argue that Wazobia gospel music—multilingual singing in Nigerian churches—embodies multilayered roles in negotiating identity and creating hospitality. The complexity of studying congregational singing in cosmopolitan cities (like Lagos, Nigeria) due to multiple ethnolinguistic and musical expressions within local and transnational links is also addressed. To tackle this complexity, this article adopts an interdisciplinary approach, combining historical research, oral history, and hybrid ethnography. This approach ensures a thorough and in-depth understanding of Wazobia gospel music, a topic of significant importance in the study of Nigerian music, linguistics, and cultural studies. By employing frameworks of musical localization and signification, I incorporate the results of my ethnographic studies of three Protestant churches in Lagos, Nigeria, to illustrate Wazobia gospel music’s continued importance. The article conceptualizes multilingual singing and offers fresh perspectives on studying Nigerian Christian congregational music in the twenty-first century.